PENGARUH STRATEGI BISNIS PROSPECTOR TERHADAP KINERJA SEKOLAH DENGAN PERAN SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL MODERATING - Nadia Birru Salma; Suwandi Suwandi (Gapenas Publisher, 2023)
This study aims to determine the effect of the prospector's business strategy on school performance, as well as the role of Accounting Information Systems in moderating prospector's business strategy on the performance of SMA-SMK level schools in Gresik Regency. The type of data used is primary data, which is quantitative data by distributing questionnaires as respondent data collection. The samples collected in this study were 54 respondents. The sampling method used in this study was purposive sampling. In this study, the Structural Equation Modeling-Partial Least Square (SEM-PLS) method was used to analyze the data as a whole with SmartPLS 3.0 software. The results of this study indicate that the Prospector Business Strategy has a significant effect on School Performance, and the Accounting Information System has no significant effect for not being able to moderate the Prospector's Business Strategy on School Performance